Potential Candidacy for Liver Transplantation among Chronic Liver Disease Patients Presenting to Khyber Teaching Hospital, Peshawar - Badshah, Aliena; Atif, Durkho (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To determine the frequency of potential candidates for liver transplantation among decompensated chronic liver parenchymal disease patients. METHODOLOGY: This cross-sectional descriptive study was conducted in the Department of Medicine at Khyber Teaching Hospital, Peshawar, from September 2021 to February 2022. The study included 200 patients with decompensated chronic liver parenchymal disease. Their eligibility for liver transplantation was determined by calculating the MELD-Na score for each of them. Eligibility for liver transplant was correlated with a higher MELD-Na score (>25). Data were collected and entered in SPSS 25. RESULTS: 168 of the 200 patients comprised those with viral hepatitis B or C (84%); 73.21% of these were hepatitis C positive, and 26.8% were hepatitis B positive; this was followed by patients with hepatocellular carcinoma (8%). 62.5% (5% of the total sample size) were HBV positive, and 37.5% (3% of the entire sample size) were HCV positive; however, HCC secondary to viral hepatitis was taken as an independent indication for a liver transplant. 4% of the patients had autoimmune hepatitis, 2% had NAFLD, and 2% were attributed to other causes. Of the 200 patients, 5% had MELD-Na score <9; 19% had MELD-Na score 10-19; 36% had MELD-Na score 20-29; 39% had MELD-Na score 30-39; 1% had MELD-Na score >40. CONCLUSION: Many patients with DCLPD are potential candidates for liver transplantation. Hence, measures are needed to establish a liver transplant centre in Khyber Pakhtunkhwa.